Quantum scattering and quasi-classical trajectory calculations for the H2 + OH ⇆ H2O + H reaction on a new potential surface - Pogrebnya, Sergei K. (2000)
Six-dimensional (6D) quantum scattering calculations of reaction probabilities are reported for the OH + H2 ⇆ H2O + H reaction. An arrangement channel hyperspherical coordinate method is used. A new potential energy surface due to Ochoa and Clary is employed. The results agree well with those calculated using the rotating bond approximation (RBA) and the quasi-classical trajectory (QCT) method. 6D quantum, RBA and QCT calculations of rate constants for the OH + H2 reaction agree well with experiment. In addition, RBA calculations of differential cross sections for the OH + D2 → HOD + D reaction and the photodetachment spectrum for H3O- also agree well with experiment. These results suggest that the new potential surface is reliable for this reason.